Osteomyelitis of the Jaw Bones and Its Mimics: Resolving the Diagnostic Enigma - Justine, Deepak; Bhalla, Ashu Seith; Manchanda, Smita; Bhutia, Ongkila; Roychoudhury, Ajoy (Indian Journal of Radiology and Imaging, 2024)
Jaw osteomyelitis is a severe inflammatory condition affecting the maxilla or mandible, posing diagnostic and therapeutic challenges. An early and accurate diagnosis is crucial to initiating appropriate treatment and preventing potential complications. Radiological imaging plays a pivotal role in diagnosing and evaluating jaw osteomyelitis, providing valuable insights into the extent of the disease and aiding clinicians in making informed decisions. One of the most important aspects of imaging is to differentiate them from the noninfectious mimics, which can closely mimic their imaging appearance. This article aims to present a comprehensive overview of imaging in jaw osteomyelitis, focusing on the critical clinical and imaging markers that distinguish it from its noninfectious imitators.
Keywords: jaw osteomyelitis; mandible; maxilla; osteoradionecrosis; osteonecrosis; CT; CRMO; Caffey disease